Hallmark features of immunosenescence are absent in familial longevity - Derhovanessian, Evelyna; Maier, Andrea B; Beck, Robert; Jahn, Gerhard; Hähnel, Karin; Slagboom, P Eline; de Craen, Anton J M; Westendorp, Rudi G J; Pawelec, Graham (The Journal of immunology (1950), 2010)
Seropositivity for CMV is one of the parameters of the "immune risk profile" associated with mortality in longitudinal studies of the very elderly and may accelerate immunosenescence. Thus, any genetic factors influencing human longevity may be associated with susceptibility to CMV and CMV-accelerated immunosenescence. To test this, we analyzed long-lived families in the Leiden Longevity Study (LLS) in which offspring enjoy a 30% reduced standardized mortality rate, possibly owing to genetic enrichment. Serum C-reactive protein levels and the frequency of different T cell subsets were compared between 97 LLS offspring and 97 controls (their partners, representing the normal population). We also determined the capacity of T cells to respond against immunodominant Ags from CMV in a smaller group of LLS subjects and controls. CMV infection was strongly associated with an age-related reduction in the frequency of naive T cells and an accumulation of CD45RA-re-expressing and late-differentiated effector memory T cells in the general population, but not in members of long-lived families. The latter also had significantly lower C-reactive protein levels, indicating a lower proinflammatory status compared with CMV-infected controls. Finally, T cells from a higher proportion of offspring mounted a proliferative response against CMV Ags, which was also of greater magnitude and broader specificity than controls. Our data suggest that these rare individuals genetically enriched for longevity are less susceptible to the characteristic CMV-associated age-driven immune alterations commonly considered to be hallmarks of immunosenescence, which might reflect better immunological control of the virus and contribute to their decreased mortality rate.